2017
DOI: 10.1039/c7ra05359b
|View full text |Cite
|
Sign up to set email alerts
|

Molecular-level insight into the binding of arginine to a zwitterionic Langmuir monolayer

Abstract: Arginine molecules bind to a DPPC monolayer, altering the interfacial electrostatic potential and the lateral mobility of the lipids, while having little effect on the compression isotherm of the monolayer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 77 publications
0
8
0
Order By: Relevance
“…The simulations were performed in an N γ P z T ensemble, being N the number of particles, T the temperature (298 K), P z the normal component of the pressure tensor (1 bar), and γ the surface tension . This ensemble allows to maintain a constant Z dimension and to adjust X and Y dimensions according to an imposed surface tension setting .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The simulations were performed in an N γ P z T ensemble, being N the number of particles, T the temperature (298 K), P z the normal component of the pressure tensor (1 bar), and γ the surface tension . This ensemble allows to maintain a constant Z dimension and to adjust X and Y dimensions according to an imposed surface tension setting .…”
Section: Methodsmentioning
confidence: 99%
“…The simulations were performed in an N γ P z T ensemble, being N the number of particles, T the temperature (298 K), P z the normal component of the pressure tensor (1 bar), and γ the surface tension . This ensemble allows to maintain a constant Z dimension and to adjust X and Y dimensions according to an imposed surface tension setting . Surface tension in MD simulations (γ MD ) is calculated from the lateral and tangential components of the pressure tensor, using the following function: γ MD = L z 0.25em ( p z z 0.5 false( p x x + p y y false) ) where L z is the length of the simulation box in the direction perpendicular to monolayers, p zz is the pressure normal to monolayers, and p xx and p yy are the pressure values in the directions parallel to the monolayers…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…18,19 We also examined the specic intermolecular interactions of DMPA with the Fmoc-amino acids and found that Fmoc-Y showed superior performance when interacting with the phospholipid surface by molecular mechanics computational simulations. 20…”
Section: Introductionmentioning
confidence: 99%